GTPases of the Rho subfamily are required for Brucella abortus internalization in nonprofessional phagocytes - Guzman-Verri, Caterina (2001)
Members of the genus Brucella are intracellular -Proteobacteria responsible for brucellosis, a chronic disease of humans and animals. Little is known about Brucella virulence mechanisms, but the abilities of these bacteria to invade and to survive within cells are decisive factors for causing disease. Transmission electron and fluorescence microscopy of infected nonprofessional phagocytic HeLa cells revealed minor membrane changes accompanied by discrete recruitment of F-actin at the site of Brucella abortus entry. Cell uptake of B. abortus was negatively affected to various degrees by actin, actin-myosin, and microtubule chemical inhibitors. Modulators of MAPKs and protein-tyrosine kinases hampered Brucella cell internalization. Inactivation of Rho small GTPases using clostridial toxins TcdB-10463, TcdB-1470, TcsL-1522, and TcdA significantly reduced the uptake of B. abortus by HeLa cells. In contrast, cytotoxic necrotizing factor from Escherichia coli, known to activate Rho, Rac, and Cdc42 small GTPases, increased the internalization of both virulent and non-virulent B. abortus. Expression of dominant-positive Rho, Rac, and Cdc42 forms in HeLa cells promoted the uptake of B. abortus, whereas expression of dominant-negative forms of these GTPases in HeLa cells hampered Brucella uptake. Cdc42 was activated upon cell contact by virulent B. abortus, but not by a noninvasive isogenic strain, as proven by affinity precipitation of active Rho, Rac, and Cdc42. The polyphasic approach used to discern the molecular events leading to Brucella internalization provides new alternatives for exploring the complexity of the signals required by intracellular pathogens for cell invasion.